Sammen går vi døden i møte - Molnes, Sven Inge (Nordisk Tidsskrift for Helseforskning, 2015)
In 2011 it was reported 29,907 people with a cancer diagnosis, and despite the fact that survival numbers increase, it is still a significant number of people who die of cancer every year. The process of dying and death is a natural part of life, but it's not always easy to deal with this. The purpose of this study was to examine how nurses experience spiritual aspects for cancer patients living at home. Data were collected using semi-structured, individual interviews with ten nurses. The interviews were analysed by means of Giorgi analytical method. The nurses said it was important to have a dialog with the patient about spiritual aspects, but several nurses had problems involving themselves in talks related to the patient’s situation and his thoughts about the death. To allow more cancer patients a good and worthy treatment in their own home, the community health services should focus more on increasing the skills related to spiritual aspects for cancer patients at home.